Advanced care planning in the early phase of COVID-19: a rapid review of the practice and policy lessons learned - Younan, Sarah; Cardona, Magnolia; Sahay, Ashlyn; Willis, Eileen; Ni Chroinin, Danielle (Frontiers in Health Services, 2023)
Background: The importance of advance care planning (ACP) has been highlighted by the advent of life-threatening COVID-19. Anecdotal evidence suggests changes in implementation of policies and procedures is needed to support uptake of ACPs. We investigated the barriers and enablers of ACP in the COVID-19 context and identify recommendations to facilitate ACP, to inform future policy and practice. Methods: We adopted the WHO recommendation of using rapid reviews for the production of actionable evidence for this study. We searched PUBMED from January 2020 to April 2021. All study designs including commentaries were included that focused on ACPs during COVID-19. Preprints/unpublished papers and Non-English language articles were excluded. Titles and abstracts were screened, full-texts were reviewed, and discrepancies resolved by discussion until consensus. Results: From amongst 343 papers screened, 123 underwent full-text review. In total, 74 papers were included, comprising commentaries (39) and primary research studies covering cohorts, reviews, case studies, and cross-sectional designs (35). The various study types and settings such as hospitals, outpatient services, aged care and community indicated widespread interest in accelerating ACP documentation to facilitate management decisions and care which is unwanted/not aligned with goals. Enablers of ACP included targeted public awareness, availability of telehealth, easy access to online tools and adopting person-centered approach, respectful of patient autonomy and values. The emerging barriers were uncertainty regarding clinical outcomes, cultural and communication difficulties, barriers associated with legal and ethical considerations, infection control restrictions, lack of time, and limited resources and support systems. Conclusion: The pandemic has provided opportunities for rapid implementation of ACP in creative ways to circumvent social distancing restrictions and high demand for health services. This review suggests the pandemic has provided some impetus to drive adaptable ACP conversations at individual, local, and international levels, affording an opportunity for longer term improvements in ACP practice and patient care.. The enablers of ACP and the accelerated adoption evident here will hopefully continue to be part of everyday practice, with or without the pandemic.